Cyberbullying and parental mediation in the context of social media - Chen, Liang (2017)
With the increasing adoption and penetration of information and communication technologies (ICT), cyberbullying has become a critical social issue, which severely threatens the physical and psychological health of children and adolescents. Despite the rapid increase in the saliency of cyberbullying in the last decade, there still remains numerous research gaps. In order to identify these research gaps, this dissertation first conducted a meta-analytic study (Study 1) to systematically examine the factors underlying cyberbullying in the existing literature. Next, in response to the research gaps identified, Study 2 was carried out to explore how parents manage their children’s social media use as well as to develop and validate a scale of parental mediation of social media. Based on this scale, Study 3 was designed to investigate the influences of parental mediation strategies, personality traits, and the third-person perception on cyberbullying on social media. Specifically, Study 1 systematically examined the predictors of cyberbullying from the social cognitive and media effects approach. This study identified and examined 16 predictors of cyberbullying perpetration and victimization. The magnitude of the effects of these predictors were meta-analyzed using 81 empirical studies, which represented a total sample of 99,741 participants and yielded 259 independent correlations. The results revealed that risky ICT use, moral disengagement, depression, social norms, and traditional bullying perpetration were the main predictors of cyberbullying perpetration, while risky ICT use and traditional bullying victimization were the major contributors of cyberbullying victimization. According to the moderator analyses, country of the sample, sampling method, age, and media platform were significant moderators of the relationships between some specific predictors and cyberbullying perpetration and victimization. The findings suggested that future research should examine cyberbullying on social media among people from different age groups (e.g., children) and different countries (e.g., Asia). In addition, according the results, two personality traits reflecting positive views of the self – self-esteem and narcissism – are important to cyberbullying. However, there are very limited studies to date that examined and compared the influences of narcissism and self-esteem on cyberbullying. Furthermore, this research clarified that although there were few studies highlighting the role of parental mediation in cyberbullying, these studies did not differentiate between the influences of different parental mediation strategies on cyberbullying. To fill in these research gaps, studies should explore how parents approach their children’s social media use, as well as how these mediation strategies and positive self-views affect cyberbullying on social media amongst children and adolescents. Building on the recommendations from Study1, Study 2 addressed the conceptualization and operationalization of parental mediation of social media. First, this study conducted focus groups with both children and parents in Singapore, which identified four conceptually distinct parental mediation strategies of social media – active mediation, restrictive mediation, authoritarian surveillance, and monitoring, and developed an initial scale for them. In order to refine and test the scale, this study conducted a survey with a representative sample of 1,424 child participants and 1,206 parent participants in Singapore. The results were analyzed using a confirmation factor analysis. Besides, the scale was confirmed and validated upon assessments of the reliability, convergence validity, and discriminant validity. Study 3 examined the associations of four different parental mediation strategies (validated in Study2) and personality traits reflecting positive self-views with cyberbullying perpetration and victimization on social media between primary and secondary school students. Potential interactive mechanisms affecting the effectiveness of parental mediation were further examined. They include the third-person perception, parent-child agreement in reporting parental mediation, and the age of the children. The results revealed that four different parental mediation strategies had varied effectiveness on preventing cyberbullying perpetration and victimization. Among these, active mediation was the most effective strategy in reducing cyberbullying perpetration, whereas restrictive mediation was more effective than others in protecting children from cyberbullying victimization. However, children under authoritarian surveillance parental mediation strategy were more likely to resist their parents’ demanding control and engage in both cyberbullying perpetration and victimization. Furthermore, the moderation results revealed that the effectiveness of some parental mediation strategies of social media was contingent upon the third-person perception and parent-child agreement in reporting parental mediation. Moreover, the parental mediation effectiveness varied between primary and secondary school students. Taken together, this dissertation provides a systematic and comprehensive view on cyberbullying. In addition, it also elucidates some effective parental mediation strategies to guard against cyberbullying as well as identifies the key factors affecting the effectiveness of parental mediation. Lastly, the findings obtained from the research studies provide both theoretical and practical contributions to the field of cyberbullying and parental mediation.